2018
DOI: 10.1089/scd.2017.0161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Morphogenetic Protein 6 on Immunomodulatory Functions of Salivary Gland-Derived Mesenchymal Stem Cells in Sjögren's Syndrome

Abstract: Sjögren's syndrome (SS) is characterized by autoimmune activation and loss of function in the salivary glands. Recent studies reported that bone morphogenetic protein 6 (BMP6), which is a member of transforming growth factor beta (TGF-β) superfamily, was highly expressed in SS patients. To investigate the role of BMP6 in SS, we treated the salivary gland-derived mesenchymal stem cells (SGMSCs) with BMP6 and found that BMP6 could impair immunomodulatory properties of normal SGMSCs by downregulating the Prostagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Confirming these observations, the overexpression of BMP6 in the SGs of genetic modified C57BL/6 mice results in a SS-like phenotype [ 126 ], although the underlying mechanism is not clear. Xu et al assumed that BMP6 could indirectly determine immune cell infiltration of SGs through the impairment of mesenchymal stem cell function [ 127 ]. Other studies suggested that BMP6-induced SG dysfunction was rather associated with an altered glandular cell water permeability or ECM protein modulation [ 125 , 126 , 128 ].…”
Section: Future Perspectives On Alternative Molecular Mechanisms Mmentioning
confidence: 99%
“…Confirming these observations, the overexpression of BMP6 in the SGs of genetic modified C57BL/6 mice results in a SS-like phenotype [ 126 ], although the underlying mechanism is not clear. Xu et al assumed that BMP6 could indirectly determine immune cell infiltration of SGs through the impairment of mesenchymal stem cell function [ 127 ]. Other studies suggested that BMP6-induced SG dysfunction was rather associated with an altered glandular cell water permeability or ECM protein modulation [ 125 , 126 , 128 ].…”
Section: Future Perspectives On Alternative Molecular Mechanisms Mmentioning
confidence: 99%
“…Although the overexpression of BMP6 creates SS-like phenotypes in animal models, the underlying mechanism is not clear [143]. Xu et al assumed that BMP6 may indirectly induce immune cell infiltration via mesenchymal stem cell function impairment [145]. Other studies suggested that BMP6-induced salivary gland dysfunction had a weak link with immune cell regulation and was rather associated with the loss of glandular cell water permeability or ECM modulation [142][143][144].…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…Anti-BMP6 targeted therapy increased the production of prostaglandin E2 (PGE2), but had no effect on other soluble factors (indoleamine 2,3-dioxygenase [IDO], nitric oxide [NO], transforming growth factor [TGF]-β). As Figure 3 shows, anti-BMP6 treatment induced an increase in PGE2 and a decrease in interferon (IFN) gamma and interleukin (IL)-17 via DNA-binding protein inhibitor (Id)1 [ 12 , 13 ]. BMP6 altered the immunomodulatory properties of SGMSCs by inhibition of proteins involved in Id1 [ 13 ].…”
Section: Resultsmentioning
confidence: 99%